Analysis Of The Influence Of Brand Image, Price, Location And Product Quality On Used Clothing Customer Satisfaction At The Monja Horas Aek Tapa Rantauprapat Store - Nurhalizah*, Siti; lubis, Junita; Hasibuan, Muhammad Irwansyah (Universitas Syiah Kuala, 2024)
In the current era of globalization, the development of the business world is increasingly rapid. One of them is business in the fashion sector. This business cannot be separated from global influence due to a situation that forces developing countries to follow the fashion of developed countries. The aim of this research is to determine the influence of brand image, price, location and product quality on customer satisfaction with used clothing at the Monja Horas Aek Tapa Rantauprapat shop. The results of the research show that brand image, price, location and product quality on used clothing customer satisfaction at the Monja Horas Aek Tapa Rantauprapat store have a significant effect on customer satisfaction partially and simultaneously.